PUTUSAN MAHKAMAH KONSTITUSI RI DAN FATWA MUI TENTANG KEDUDUKAN ANAK ZINA (ANALISIS KOMPARATIF) - M Halilurrahman; Abdul Wahid (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2019)
All decisions made by the Constitutional Court are final, binding and not have a remedy for the review. On February 17, 2012, the Constitutional Court issued a ruling number: 46/PUU-VIII/2010 about the position of children outside the marriage. This ruling invites controversy among the community. And a very interesting of this ruling is the reaction of the Indonesia Ulama Council issued a fatwa number: 11/CONGRESS VIII/MUI/3/2012 about the position of children of adultery and the treatment of him. This Fatwa is a reaction to the rejection of The the Indonesia Ulama Council against the verdict of the Constitutional Court in reviewing appropriate Islamic jurisprudence.